2020
DOI: 10.1002/jca.21868
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory myasthenia gravis by double‐filtration plasmapheresis and rituximab: A case series of nine patients and literature review

Abstract: Introduction Myasthenia gravis (MG) is an autoimmune disease mediated by circulating autoantibodies (anti‐AchR, anti‐MuSK, etc.). More than 20% of myasthenic patients are refractory to conventional treatments (plasma exchange, IVIg, steroids, azathioprine, mycophenolate mofetil). Rituximab (B‐lymphocyte‐depleting anti‐CD20) and apheresis (double‐filtration plasmapheresis [DFPP] and immunoadsorption [IA]) are interesting therapeutic alternatives. Methods This monocentric pilot study included nine refractory mya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…An important research perspective could be to study the best combinations between nanomembrane-based TPE and other treatments. For example, the combination of double-filtration plasmapheresis and rituximab was proven to be effective in treatment of refractory MG [ 37 ], as were our combination of nanomembrane-based TPE and IVIG in this clinical scenario. The combination using double-filtration plasmapheresis proved to be more effective in lowering IgA levels than one using immunoabsorption [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important research perspective could be to study the best combinations between nanomembrane-based TPE and other treatments. For example, the combination of double-filtration plasmapheresis and rituximab was proven to be effective in treatment of refractory MG [ 37 ], as were our combination of nanomembrane-based TPE and IVIG in this clinical scenario. The combination using double-filtration plasmapheresis proved to be more effective in lowering IgA levels than one using immunoabsorption [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of double-filtration plasmapheresis and rituximab was proven to be effective in treatment of refractory MG [ 37 ], as were our combination of nanomembrane-based TPE and IVIG in this clinical scenario. The combination using double-filtration plasmapheresis proved to be more effective in lowering IgA levels than one using immunoabsorption [ 37 ]. The choice of these possible (but not exclusive) combinations could be influenced by the IgA levels.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review has also demonstrated the success of this approach in treating refractory cases of myasthenia gravis (MG), another autoimmune condition. Nine patients with refractory MG who were treated with plasmapheresis and rituximab showed an overall decrease in disease severity, long-term clinical improvement, and self-sufficiency [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DFPP technique allows pathophysiological relevant molecules (e.g., circulating autoantigens, autoantibodies, circulating immune complexes, damaged proteins) and toxins (e.g., environmental toxins and toxins from microorganisms) to be removed from the blood of a subject. This blood cleaning procedure has been successfully used therapeutically in many diseases [2][3][4], including myasthenia gravis [5][6][7][8][9][10][11][12], chronic inflammatory demyelinating polyneuropathy [12], anti-glomerular basement membrane disease [13], hypoglycemia and hyperglycemia induced by insulin antibodies [14], pancreatitis induced by hypertriglyceridemia [15][16][17], Guillain-Barré syndrome [12,[18][19][20][21], Crow-Fukase syndrome [12], rheumatoid arthritis [22][23][24], chronic hepatitis C [25,26], pemphigus [27,28], bullous pemphigoid [29,30], atopic dermatitis [31], dermatomyositis [12], polymyositis [12], membranous nephropathy [32], acute thallotoxicosis [33], antibody-associated vasculitis [34][35][36], antisynthetase syndrome [37], diffuse proliferative lupus nephritis…”
Section: Introductionmentioning
confidence: 99%